Optimization of 4G LTE Network with Automatic Cell Planning and Carrier Aggregation Methods - Sutoyo Sutoyo; Teddy Purnamirza; Mulyono Mulyono; Ahmad Faizal (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2024)
The implementation of 4G LTE in Indonesia still faces numerous challenges, particularly in terms of coverage areas that are less than optimal, causing many areas to be classified as bad spots. One of them is Koto Baru Payobasung area, Payakumbuh. Network optimization is one method for overcoming this problem. In this study, we will use optimization techniques such as Automatic Cell Planning (ACP) and Carrier Aggregation (CA) with RSRP, SINR, and Throughput parameters. Through existing simulations, the results of the initial research revealed that two of the three parameters, namely RSRP and Throughput, were classified as very bad conditions. Based on the results of optimization using the ACP technique, it was discovered that there was an increase in the RSRP value of = -103 dBm, SINR of = 2 dB, and Throughput = 15 mbps. The RSRP value for the CA technique is -90 dBm, the SINR is 7 dB, and the throughput is 50 mbps. Because of the value of the optimization parameter results, the CA technique is more effective than the ACP technique in these two optimization techniques